Kindfulness : be a true friend to yourself - with mindful self-compassion /? - O'Morain, Padraig
In this practical and uplifting guide psychotherapist and leading mindfulness expert Padraig O'Morain offers simple yet effective exercises to help you give yourself the gift of self-compassion. By making kindfulness your ally, you will learn how to be